IMPLEMENTASI MANAJEMEN PROGRAM PENDIDIKAN GURU PENGGERAK JENJANG TK DI KOTA PEKANBARU - Ratnawati, Ratnawati; Chairilsyah, Daviq; Suanto, Elfis (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2025)
Quality education is the key to creating superior and competitive human resources. The Teacher Leader Education Program is one of the initiatives of the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia to improve teacher competence and encourage positive changes in the education sector. This study aims to analyze the management of the teacher leader education program at the kindergarten level in Pekanbaru City, which involves two schools, namely TK Negeri Pembina 1 and TK Negeri Pembina 3. This study uses a descriptive qualitative approach, with data collection techniques through in-depth interviews, documentation, and observation. Research informants include teacher leaders, principals, and colleagues who are directly involved in the program. The results of the study indicate that the implementation of the teacher leader education program in Pekanbaru City faces various challenges such as resistance to change and lack of support and time to carry out tasks. However, this program has succeeded in providing a positive impact in improving teacher pedagogical competence and creating a more innovative and effective learning environment. Good program implementation requires ongoing support from various parties, including facilitators, mentors, and the education community. Periodic evaluation and continuous improvement are needed to ensure that this program can achieve its goals optimally and make a real contribution to improving the quality of education in Indonesia.